The acaulescent rosette species of Lupinus L. (Fabaceae) of Colombia and Ecuador including a new species from Colombia - Contreras-Ortiz, Natalia; Jara-Muñoz, Orlando A.; Hughes, Colin E. (Phytotaxa, 2018)
We present a taxonomic synopsis of the acaulescent rosette species of Lupinus from Colombia and Ecuador, including a checklist with revised nomenclature and a key to species. A new species, Lupinus luisanae, and a variety of this species, L. luisanae var. ocetensis, endemic to the northern portion of the Eastern Cordillera of the Colombian Andes, are described and illustrated. Lupinus inflatus is proposed as a new synonym of L. nubigenus.